The Midsummer Drought over Mexico and Central America - Amador Astúa, Jorge Alberto (1998)
The annual cycle of precipitation over the southern part of Mexico and Central America exhibits a bimodal distribution with maxima during June and September–October and a relative minimum during July and August, known as the midsummer drought (MSD). The MSD is not associated with the meridional migration of the intertropical convergence zone (ITCZ) and its double crossing over Central America but rather with fluctuations in the intensity and location of the eastern Pacific ITCZ. During the transition from intense to weak (weak to intense) convective activity, the trade winds over the Caribbean strengthen (weaken). Such acceleration in the trade winds is part of the dynamic response of the low-level atmosphere to the magnitude of the convective forcing in the ITCZ. The intensification of the trade winds during July and August and the orographic forcing of the mountains over most of Central America result in maximum precipitation along the Caribbean coast and minimum precipitation along the Pacific coast of Central America. Changes in the divergent (convergent) low-level winds over the ‘‘warm pool’’ off the west coast of southern Mexico and Central America determine the evolution of the MSD. Maximum deep convective activity over the northern equatorial eastern Pacific, during the onset of the summer rainy season, is reached when sea surface temperatures exceed 298C (around May). After this, the SSTs over the eastern Pacific warm pool decrease around 18C due to diminished downwelling solar radiation and stronger easterly winds (during July and August). Such SST changes near 288C result in an substantial decrease in deep convective activity, associated with the nonlinear interaction between SST and deep tropical convection. Decreased deep tropical convection allows increased downwelling solar radiation and a slight increase in SSTs, which reach a second maximum (;28.58C) by the end of August and early September. This increase in SST results once again in stronger low-level convergence, enhanced deep convection, and, consequently, in a second maximum in precipitation. The MSD signal can also be detected in other variables such as minimum and maximum surface temperature and even in tropical cyclone activity over the eastern Pacific.